Control of Rhyzopertha dominica using a controlled atmosphere with CO2, in wheat - Gonçalves, Rogério Amaro; Santos, Jamilton Pereira; Chandra, Prabir Kumar; Germani, Rogério (Pesquisa Agropecuaria Brasileira, 2000)
Controlled atmosphere with inert gases offers an alternative to phosphine use to control stored grain pests. The objective of this research was to test a controlled atmosphere with CO2 to control Rhyzoperta dominica, (Fabr.) (Coleoptera: Bostrichidae), an important pest of stored wheat grain. This test consisted of five CO2 concentrations ( 0, 30, 40, 50 and 60%; completed with N2), fumigation periods of 5, 10 and 15 days; insect populations collected from Campo Mourão, PR, Sete Lagoas, MG and Santa Rosa, RS, in Brazil, and seven developing stages (egg, larva of 1st, 2nd, 3rd and 4th instar, pupa and adult), in three replications. All the different life stages of the insect were kept as individual samples in a small voile cloth bag and put inside a 200 liter fumigation chamber with 75% of this volume full of grain with the metal lid sealed at the edge with silicone rubber to guarantee hermetic conditions. The different CO2 concentrations were then added inside the chambers. The results showed that all CO2 concentrations tested caused 100% mortality to all adult stage of the three insect populations in all fumigation periods tested. The mortality of the pupa stage of the three insect population was 100% when the 60% CO2 concentration was used in the 15 days fumigation period; however, all CO2 concentrations in 15 days fumigation period caused 100% mortality in pupa of insects collected in Santa Rosa. For adequate control of all larval stages it requires 50% CO2 or above this concentration. During the 10 and 15 days fumigation periods all CO2 concentrations controlled 100% of the eggs from the three populations studied.